Application Address Book Criteria Based and Mail Printing Chosen by Address - author author (Jurnal Sistem Informasi, 2007)
In this writing, the author only discusses how the address book application that includes an address maintenan type, input data, edit data, search for records based on criteria as well as printing a letter based on the selected address. Specific purpose of writing is making the application program as a support to facilitate the work the author as a personal assistant. With the existence of these applications is expected to be a means of support for a private secretary. And also can alleviate the problems that writers face and useful for others who face the same problem with the author. The general objectives of this paper is to deepen the science writers of visual basic programming language, as well as students complete the task.